Latent Class Analysis of the Child Behavior Checklist Obsessive-Compulsive Scale - Althoff, Robert R. (2009)
The Obsessive Compulsive Scale (OCS) of the Child Behavior Checklist (CBCL) predicts Obsessive-Compulsive Disorder and is highly heritable. Latent Class Analysis (LCA) of the OCS was used to identify profiles within this 8-item scale and to examine heritability of those profiles. LCA was performed on maternal CBCL reports of their 6–18 year-old children from 2 U.S. nationally representative samples from 1989 (n=2475, 50% male) and 1999 (n=2029, 53% male) and from Dutch Twins in the Netherlands Twin Registry at ages 7 (n=10,194, 49.3% male), 10 (n=6448, 48.1% male), and 12 (n=3674, 48.6% male). The heritability of the resultant classes was estimated using odds ratios of twin membership across classes. A 4-class solution fit all samples best. The resulting classes were a “no or few symptoms” class, a “worries and has to be perfect” class, a “thought problems class, and an “OCS” class. Within class odds ratios were higher than across class odds ratios and were higher for MZ than DZ twins. We conclude that LCA identifies an OCS class and that class is highly heritable using across-twin comparisons.